Process development and safety evaluation of ABCB5+ limbal stem cells as advanced-therapy medicinal product to treat limbal stem cell deficiency - Norrick, Alexandra; Esterlechner, Jasmina; Niebergall-Roth, Elke; Dehio, Ulf; Sadeghi, Samar; Schröder, Hannes M.; Ballikaya, Seda; Stemler, Nicole; Ganss, Christoph; Dieter, Kathrin; Dachtler, Ann-Kathrin; Merz, Patrick; et al. (Stem cell research & therapy, 2021)
While therapeutic success of the limbal tissue or cell transplantation to treat severe cases of limbal stem cell (LSC) deficiency (LSCD) strongly depends on the percentage of LSCs within the transplanted cells, prospective LSC enrichment has been hampered by the intranuclear localization of the previously reported LSC marker p63. The recent identification of the ATP-binding cassette transporter ABCB5 as a plasma membrane-spanning marker of LSCs that are capable of restoring the cornea and the development of an antibody directed against an extracellular loop of the ABCB5 molecule stimulated us to develop a novel treatment strategy based on the utilization of in vitro expanded allogeneic ABCB5+ LSCs derived from human cadaveric limbal tissue.
Im Titel ist "+" hochgestellt
Gesehen am 16.04.2021